The precipitation patterns and atmospheric dynamics of the Serengeti National Park - Mahony, J; Dyer, E; Washington, R (Wiley, 2020)
The unique precipitation patterns over the Serengeti National Park in East Africa form the foundation of an internationally important ecosystem. Quantifying these precipitation patterns, and identifying the causal atmospheric processes, can improve understanding of past and future changes to regional rainfall. Precipitation and reanalysis datasets (CHIRPS v2.0, TRMM 3B42, ERA5) were used to quantify the regional climatic conditions on annual, monthly and hourly timescales. Hierarchical cluster analysis identified regions with distinct annual cycles of precipitation. Annual and monthly precipitation over the wider Serengeti domain (1°–4°S, 33°–37°E) was spatially heterogeneous. Cluster analysis identified five sub-regions with distinct annual cycles, with differing rainfall totals during January–February and June–September, wet season peak rainfall months, and rainfall peak symmetry. Seasonality was broadly controlled by the biannual passage of the tropical rainfall belt. Low-level wind, humidity and convergence patterns were impacted by the topography and Lake Victoria. An afternoon convergence zone between tropical easterlies and lake breeze winds always ran through the park and was associated with ascending motion and convection. The spatial progression of diurnal rainfall over the Serengeti followed the direction of 750 hPa tropical easterlies. The majority of the park received a late-afternoon rainfall peak, but from October to March an early afternoon peak was present between the wind convergence line over the central Serengeti and the rift topography. We propose that interactions between tropical easterlies, lake breeze westerlies and the topography control the spatial distribution of Serengeti precipitation, and that the seasonally changing rainfall gradient over the Serengeti may be generated by storms forming at the lake front and propagating in the direction of tropospheric easterlies. We suggest the early precipitation peak in the eastern Serengeti may be due to variability in the position of the lake front, or small storms generated by localized solar heating.